Purse-string suture technique using a mini-Pfannenstiel incision to treat large dermoid cysts - Atilgan, Remzi; Pala, Sehmus; Bulu, Gulay (Taylor & Francis Inc, 2020)
This study describes the purse-string suture technique using a mini-Pfannenstiel incision for the surgical treatment of large ovarian dermoid cysts. We investigated intra and postoperative outcomes in 24 patients who underwent removal of large ovarian dermoid cysts through a mini-Pfannenstiel incision using the purse-string suture technique. The surgical procedure was performed by two experienced surgeons. The mean diameter of the cysts was 11.9 cm. The mean operation time was 46 min and the intraoperative rupture rate was 8.3%. No patient developed chemical peritonitis. The length of hospitalisation was 36 h. The recurrence rate was 8.3% in the same ovary at 1-year follow-up. In conclusion, ovarian dermoid cysts measuring >8 cm in diameter can be effectively treated through a mini-Pfannenstiel incision using the purse-string suture technique.Impact Statement What is already known on this subject? Dermoid cysts are the most common ovarian germ cell tumours occurring in the second and third decades of life, and these tumours are usually treated surgically. There is a lack of consensus among gynaecologists regarding the optimal surgical treatment modalities for ovarian dermoid cysts; however, laparoscopic cystectomy is the gold standard for the surgical treatment of dermoid cysts. Notably, aspiration of dense cystic contents may be difficult during laparoscopic cystectomy. What do the results of this study add? Our technique enables easy removal of dense cystic materials including hair and bone fragments. The short operation time, low recurrence rate and the minimal incisional scar serve as advantages of our novel method.
Keywords: Ovarian dermoid cyst; mini-Pfannenstiel incision; purse-string suture